Phylogenetic relationship of a fossil macaque (Macaca cf. robusta) from the Korean Peninsula to extant species of macaques based on zygomaxillary morphology. Issue 119 (June 2018) - Ito, Tsuyoshi; Lee, Yung-jo; Nishimura, Takeshi D.; Tanaka, Mikiko; Woo, Jong-yoon; Takai, Masanaru
Abstract: Little is known about the biogeographical and evolutionary histories of macaques ( Macaca spp.) in East Asia because the phylogenetic positions of fossil species remain unclear. Here we examined the zygomaxillary remains of a fossil macaque ( M. cf. robusta ) from the Durubong Cave Complex, South Korea, that dates back to the late Middle to Late Pleistocene, to infer its phylogenetic relationship to extant species. We took 195 fixed- and semi-landmarks from the zygomaxillary regions of the fossil specimen and from 147 specimens belonging to 14 extant species. We then conducted a generalized Procrustes analysis followed by a multivariate statistical analysis to evaluate the phenetic affinities of the fossil to the extant species and reconstructed the most parsimonious phylogenetic tree using a phylogenetic morphometric approach. We found that the fossil was most similar to Macaca fuscata (Japanese macaque) in the zygomaxillary morphospace although it was at the limit of the range of variation for this species. The second closest in the morphospace was the continental Macaca mulatta (rhesus macaque). Parsimonious reconstruction confirmed that the fossil was most closely related to M. fuscata, even after controlling for the effects of allometry. These findings suggest that in the late Middle to Late Pleistocene, close relatives of M. fuscata that looked like the extant species were distributed on the Korean Peninsula, where no species of macaques are found today. Thus, some morphological characteristics of M. fuscata may have developed before its ancestor dispersed into the Japanese archipelago.